Weibull Reliability Methodology for Ball Bearing Design Based on Hertz Stress With Focus on Industry 4.0 - Villa Covarrubias, Baldomero; Rico, Lazaro; Piña Monarrez, Manuel Román (El Colegio de Chihuahua, 2021)
The fourth industrial revolution, also known as Industry 4.0, is characterized by the digitalization of processes and use of technologies for manufacturing along with the combination of production processes and machines using internet, software and sensors is common. Since many of the mechanical elements of machines like bearings, screws, springs, gears, and pulleys are prone to failures or requiere constant maintenance, Industry 4.0 allows an analysis and provides instant feedbacks of the problems. Thus, when the process machines are interconnected and available, fewer failures will surface due to instantaneous feedback. Consequently, maintenance programs need to be rigorously designed, implemented and monitored. Moreover, there exist various types of maintenance such as preventive, corrective and predictive. The latter is the maintenance that is more commonly used in Industry